ANALISA PENGARUH KUALITAS SINKAD DAN LAYANAN TERHADAP KEPUASAN MAHASISWA LEMBAGA PENDIDIKAN WEARNES EDUCATION CENTER MALANG - yuniar fitriyani; Fathorrahman Fathorrahman; Theresia Pradiani (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2019)
This research intends to analyze student satisfaction that is influenced by the quality of information and the SINKAD system, academic and non-academic services where the research was conducted at the Malang Wearnes Education Center Education Institute.